Modeling and Simulation of Biodiesel Transesterification Reactor - Ahmed, Duraid Fadhil (Journal of Advanced Research in Instrumentation and Control Engineering; Vol 11 No 3&4 (2024): Journal of Advanced Research in Instrumentation and Control Engineering, 2025)
The present work deals with studying the dynamic behavior. The Oil reacting methanol to produced Biodiesel. A mathematical model for the Biodiesel Transesterification Reactor is derived based on mass balance and energy balance triglyceride (TG),diglyceride (DG),mono glyceride (MG),glyceride (G), Alkyl Ester (E)and Methanol inside the reactor. The simulation of the Biodiesel Transesterification Reactor is solved by using ''MATLAB/Simulink''. The dynamic model of the open- loop system is implemented by measuring the exit reactor temperature, exit concentration of triglyceride , alkyl ester (Biodiesel) and exit concentration of glycerol responses of Biodiesel Transesterification Reactor to a step-change disturbances in the feed triglyceride concentration from 1.11 kmol/m3 to 1.22 kmol/m3, 1.33 kmol/m3, 1.44 kmol/m3, 1.55 kmol/m3, 1.67 kmol/m3, 1 kmol/m3, 0.89 kmol/m3, 0.79 kmol/m3,0.67 kmol/m3 and 0.56 kmol/m3, feed methanol concentration from 6.66 kmol/m3 to 7.33 kmol/m3, 7.99 kmol/m3, 8.66 kmol/m3, 9.3 kmol/m3, 10 kmol/m3, 5.99 kmol/m3, 5.33 kmol/m3, 4.66 kmol/m3,3.97 kmol/m3 and 3.33 kmol/m3, volumetric flow rate from 27.08 m3/hr to 30 m3/hr, 35m3/hr, 40 m3/hr, 45 m3/hr, 22 m3/hr ,20 m3/hr, 18 m3/hr and 15 m3/hr and feed temperature from 333 K to 335 K, 338 K, 328 K, 323 K, 318 K and 313 K. The simulation results of the open-loop system showed that the sensitivity index value when the methanol is stepped from 6.66 kmol/m3 to 7.33 kmol/m3, 7.99 kmol/m3, 8.66 kmol/m3, 9.3 kmol/m3, 10 kmol/m3, 5.99 kmol/m3, 5.33 kmol/m3, 4.66 kmol/m3,3.97 kmol/m3 and 3.33 kmol/m3 is higher than from the other input variable. The results of model simulation were compared with the simulation data achieved by Mjalli, 2009 to validate the model. The results showed excellent agreement between the simulation model and simulation data of mjalli.